Effect of pH on H&E Staining of Rats Intestinal Tissue - Mohd Radzuan, Hazulin; Wan Omar, Wan Fatein Nabeila; Halim, Mohd Dhiyaulhaq (2021)
This poster was submitted to Kuantan Research Day (KRD) 2020 poster competition that was held in International Islamic University Malaysia, Kuantan Campus from 17-23rd December 2020. It reported that the pH of hematoxylin solution plays an important role in affecting the quality of histological slides as differences in hues intensity may lead to misinterpretation of the outcome.